A Metal‐Organic Framework (MOF)‐Based Multifunctional Cargo Vehicle for Reactive‐Gas Delivery and Catalysis. (26th January 2022) - Kittikhunnatham, Preecha; Leith, Gabrielle A.; Mathur, Abhijai; Naglic, Jennifer K.; Martin, Corey R.; Park, Kyoung Chul; McCullough, Katherine; Jayaweera, H. D. A. Chathumal; Corkill, Ryan E.; Lauterbach, Jochen; Karakalos, Stavros G.; Smith, Mark D.; et al.
Abstract: The efficient delivery of reactive and toxic gaseous reagents to organic reactions was studied using metal‐organic frameworks (MOFs). The simultaneous cargo vehicle and catalytic capabilities of several MOFs were probed for the first time using the examples of aromatization, aminocarbonylation, and carbonylative Suzuki–Miyaura coupling reactions. These reactions highlight that MOFs can serve a dual role as a gas cargo vehicle and a catalyst, leading to product formation with yields similar to reactions employing pure gases. Furthermore, the MOFs can be recycled without sacrificing product yield, while simultaneously maintaining crystallinity. The reported findings were supported crystallographically and spectroscopically (e.g., diffuse reflectance infrared Fourier transform spectroscopy), foreshadowing a pathway for the development of multifunctional MOF‐based reagent‐catalyst cargo vessels for reactive gas reagents as an attractive alternative to the use of toxic pure gases or gas generators. Abstract : Multifaceted metal‐organic frameworks (MOFs) can act as a food truck to adsorb, store, and deliver toxic gases to organic reactions. We showcase the versatility of MOFs by employing them as a safe‐delivery tool, while simultaneously catalyzing organic reactions, producing yields and conversions that are comparable to the reactions utilizing the toxic gases directly.